Community support groups for men living with depression: barriers and facilitators in access and engagement with services. Issue 1 (2nd January 2022) - Gosling, Rebecca; Parry, Sarah; Stamou, Vasileios
ABSTRACT: Approximately 10% of the general population will experience depression in adulthood. Concerningly, men with depression are more likely to take their own lives and less likely to seek professional support. Given men's preference for community-based support, this study employed interviews with service providers to explore the barriers and facilitators involved in community support groups for men living with depression. Nine interviews were conducted with service providers across Greater Manchester, UK. Data were analyzed via thematic analysis and revealed four themes: 'Mental Health as a Weakness, ' 'Empowering Practice, ' 'Trust and Security' and 'Group Support as a Gateway to Treatment.' Men living with depression experience identity conflict, which reduces help-seeking. Community support groups facilitate access and engagement with treatment by providing safe spaces to resolve internal conflicts. Gender-specific group support may facilitate access to support and address long waiting lists of statutory services. Implications for practice, policy and future research are discussed.